Outcome after surgical embolectomy for acute pulmonary embolism. Issue 8 (August 2022) - Panholzer, Bernd; Gravert, Hanna; Borzikowsky, Christoph; Huenges, Katharina; Schoettler, Jan; Schoeneich, Felix; Attmann, Tim; Haneya, Assad; Frank, Derk; Cremer, Jochen; Grothusen, Christina
Abstract : Aims: Patients with pulmonary embolism (PE) and contraindications for or failed thrombolysis are at the highest risk for PE-related fatal events. These patients may benefit from surgical embolectomy, but data concerning this approach are still limited. Methods: The method used here was retrospective data analysis of 103 patients who underwent surgical embolectomy from 2002 to 2020 at our department. Results: Mean age was 58.4 (±15.1) years. Fifty-eight (56.3%) patients had undergone recent surgery; the surgery was tumor associated in 32 (31.1%) cases. Thirty (29.1%) patients had to be resuscitated due to PE, and 13 (12.6%) patients underwent thrombolysis prior to pulmonary embolectomy. Fifteen (14.5%) patients were placed on extra corporeal membrane oxygenation (ECMO) peri-operatively. Five patients (4.9%) died intra-operatively. Neurological symptoms occurred in four patients (3.9%). Thirty-day mortality was 23.3% ( n = 24). Re-thoracotomy due to bleeding was necessary in 12 (11.6%) patients. This parameter was also identified as an independent risk factor for mortality. Conclusion: Surgical pulmonary embolectomy resulted in survival of the majority of patients with PE and contraindications for or failed thrombolysis. Given the excessive mortality when left untreated, an operative approach should become a routine part of discussions concerning alternative treatment options for these patients.